Qawāʿid Dafʿ Tazāhum al-Wājibāt wa Taṭbīqātuhā - al-Zanki, Salih Q. Karim; Saad Khadir, Fatima Tariq Mohamed (UIN Raden Mas Said Surakarta, 2020)
Duties are legitimate interests, and the principle in interests is to do them all or to do extra more unless this is not possible. TheÂ MukallafÂ may have more than one Islamic duty to perform, while he may not be able to perform them all. What can he do in this situation? What depiction of the issue of crowding-out of duties? and how did the scholars tackle the issue of overcrowding of duties? There were many previous studies that discussed the subject of the jurisprudence of priorities relating to our study question, but it does not discuss it in detail, analysis, and representation. The study adopted the analytical approach through the study of the Islamic texts, independent reasoning, and fatwas related to the study, and the inductive approach by researching the Islamic texts, evidence, and the branches of Jurisprudence, and drawing rules from them. The study concluded the results that there are rules that help theÂ MukallafÂ to pay the competition between the duties, by providing the highest, the strongest, and the first in order to prioritize the most important duty to what is below it whenever there is an accumulation of duties.